Pemanfaatan Alat Pendeteksi Kelembaban Tanah dan Suhu Pohon Mangrove Berbasis IoT - Ilamsyah; Jawahir; Miftahul Akhyar (Jurnal Teknik Informatika, 2022)
Abstract- Each plant has an optimal range of soil that is conducive to supporting good plant growth. Soil moisture is a measure of the health of the soil, the water content present in a given area of the soil. All plants must be within a certain range of soil moisture — most plants thrive in soils with humidity levels ranging between 20% and 60%. Regulating soil moisture is very important because the water content in the soil is a solvent, which means it breaks down the nutrients and minerals that plants need from the soil, allowing plants to absorb these beneficial particles into the plant system itself. the lack of handling in regulating humidity makes the mangrove tree less well-maintained. The research was conducted by first analyzing the problem to determine the appropriate solution. In this case is the manufacture of a tool to measure soil moisture. The development method used is the Research And Development (R&D) method as an approach in order to gather knowledge to create new products or find new ways to improve existing products and services. The application of the soil moisture sensor is expected to help in the care of mangrove plants and can save the water used for watering plants. Keywords: Mangrove, Research And Development, ESP8266   Abstrak - Setiap tanaman memiliki kisaran optimal tanah yang kondusif untuk mendukung pertumbuhan tanaman yang baik. Kelembaban tanah adalah ukuran kesehatan tanah, kandungan air yang ada di area tertentu dari tanah. Semua tanaman harus berada dalam kisaran kelembaban tanah tertentu — sebagian besar tanaman tumbuh subur di tanah dengan tingkat kelembaban yang berkisar antara 20% dan 60%. Mengaur kelembaban tanah sangat penting karena kandungan air dalam tanah adalah pelarut, yang berarti memecah nutrisi dan mineral yang dibutuhkan tanaman dari tanah, memungkinkan tanaman untuk menyerap partikel bermanfaat ini ke dalam system tanaman itu sendiri. kurangnya penanganan dalam pengaturan kelembaban membuat pohon mangrove tersebut menjadi kurang terawat. Penelitian dilakukan dengan terlebih dahulu melakukan Analisa masalah untuk selanjutnya ditentukan solusi yang tepat. Dalah hal ini adalah pembuatan alat untuk mengukur kelembaban tanahl. metode pengembangan yang digunakan adalah metode Research And Development (R&D) sebagai pendekatan dalam rangka mengumpulkan pengetahuan untuk membuat produk baru atau menemukan cara baru untuk meningkatkan produk dan layanan yang sudah ada. Aplikasi dari sensor kelembaban tanah diharapkan dapat membantu perawatan tanaman mangrove dan mampu menghemat air yang digunakan untuk menyiram tanaman. Kata Kunci : Mangrove, Research And Development, ESP8266